2020
DOI: 10.7759/cureus.10436
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Receptors and Their Relationship With Chronic Pain: A Narrative Review

Abstract: The burden of chronic pain has affected many individuals leading to distress and discomfort, alongside numerous side effects with conventional therapeutic approaches. Cannabinoid receptors are naturally found in the human body and have long been an interest in antinociception. These include CB1 and CB2 receptors, which are promising candidates for the treatment of chronic inflammatory pain. The mechanism of action of the receptors and how they approach pain control in inflammatory conditions show that it can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…The endocannabinoids act as ligands at cannabinoid receptors CB1 and CB2; CB1 receptors are predominantly expressed in the central nervous system (CNS), whereas CB2 receptors are found mostly outside the CNS. Abundant preclinical data support that when these receptors are activated, pain stimulus is suppressed, influencing nociception [ 7 , 15 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The endocannabinoids act as ligands at cannabinoid receptors CB1 and CB2; CB1 receptors are predominantly expressed in the central nervous system (CNS), whereas CB2 receptors are found mostly outside the CNS. Abundant preclinical data support that when these receptors are activated, pain stimulus is suppressed, influencing nociception [ 7 , 15 ].…”
Section: Reviewmentioning
confidence: 99%
“…Moreover, activation of these receptors is believed to have anti-nociceptive effects in controlling the human perception of pain. Studies have also shown, these receptors play an important anti-inflammatory role in chronic pain conditions [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Together with a neuroprotective quality, this effect was also found in a recent systematic review on the outcome of CBD intake in relation to its potential use as a sport-enhancing performance substance ( McCartney et al, 2020 ). It still is unclear how CBD acts in relation to the pain cascade and pathways ( Anthony et al, 2020 ). CBD has shown its potential to treat and manage pain in diseases and pain disorders, and based on this evidence CBD seems to have a potential effect on treating swelling and preventing soreness after strenuous exercise, but more evidence is required to make a clear statement.…”
Section: Pain and Sorenessmentioning
confidence: 99%
“…The components of the endocannabinoid system play a key modulatory role in nociception [1,5]. Cannabinoid receptors and ligands are expressed ubiquitously throughout the pain processing pathways, from peripheral sites, such as peripheral nerves and immune cells, to central integration sites such as the spinal cord, and higher brain regions [1,5].…”
Section: Introductionmentioning
confidence: 99%